Genetic studies of the velC gene required for proper sexual development in Aspergillus nidulans - Kim, Tae Won (My University, 2010)
VelC is required for the proper fungal development in Aspergillus nidulans. Velvet proteins, VeA, VosA, VelB, and VelC, are a new protein family in many filamentous fungi. They regulate fungal development and secondary metabolites in filamentous fungi and are also speculated to be a new class of the fungus specific transcription factor. Among velvet proteins, VelC (VeA like protein C) is the newly found protein and is not characterized yet. To test the hypothesis that VelC regulates the fungal development in A. nidulans, we generated deletion velC strain (delta-velC), and overexpression velC strains (OEvelC). We also studied the phenotypes of wild type (WT), delta-velC, and OEvelC. In both light and dark conditions, sexual development was repressed and asexual development was enhanced in delta-velC. Levels of brlA, abaA, and wetA mRNA expression in asexual developmental stage are higher in delta-velC strain. OEvelC strains resulted in highly increased number of cleistothecia (sexual structure) and less number of conidia (asexual spores). From the study of delta-velC and OEvelC, we concluded that velC functions as the posittve regulator of sexual development.
Abstract: 2 p. Complete paper: 28 p.
Keywords: Bacteriology; Biochemistry